Lessons Learned From the Affordable Care Act: The Premium Subsidy Design May Promote Adverse Selection. (December 2018) - Graetz, Ilana; McKillop, Caitlin N.; Kaplan, Cameron M.; Waters, Teresa M.
Since 2014, average premiums for health plans available in the Affordable Care Act marketplaces have increased. We examine how premium price changes affected the amount consumers pay after subsidies for the lowest-cost bronze and silver plans available by age in the federally facilitated exchanges. Between 2015 and 2016, benchmark plan premiums increased in 83.3% of counties. Overall, rising benchmark premiums were associated with lower average after-subsidy premiums for the lowest-cost bronze and silver plans for older subsidy-eligible adults, but with higher after-subsidy premiums for younger adults purchasing the same plans, regardless of income. With recent discussions to replace or overhaul the Affordable Care Act, it is critical that we learn from the successes and failures of the current policy. Our findings suggest that the subsidy design, which makes rising premiums costlier for younger adults looking to purchase an entry-level plan, may be contributing to adverse selection and instability in the marketplace.